Efficacy and safety of pregabalin in the management of low back pain: a comprehensive meta-analysis - Cordero‐García, Carlos; Sánchez‐Raya, Judith; Rodríguez‐Araya, Tamara L.; López‐Alarcón, María Dolores; Trillo‐Calvo, Eva; Balsalobre‐Aznar, Jerónimo; Pérez‐Páramo, Maria (Frontiers in Pharmacology, 2025)
IntroductionLow back pain (LBP) is one of the most prevalent chronic pain conditions that affects nearly 50% of the population. Its complex pathophysiology may involve both nociceptive and neuropathic mechanisms and is often resistant to standard treatment. Pregabalin has emerged as a potential alternative owing to its mechanism of action, the inhibition of excitatory neurotransmitter release. This meta-analysis aimed to evaluate the efficacy and safety of pregabalin in managing LBP.MethodsA systematic review of three major databases was conducted following the PRISMA guidelines. Studies were included if they were comparative studies of pregabalin with placebo or other pain medications, focusing on adult patients with LBP. Data were extracted on efficacy outcomes including pain reduction, anxiety, depression, quality of life, quality of sleep, disability, and adverse events. Statistical analysis was performed using Review Manager 5.4.1.ResultsA total of 18 studies (n = 5,000) were included. Pregabalin demonstrated significant pain reduction at 4 weeks (Standardized Mean Difference (SMD) = −0.64, 95% Confidence Interval (CI) = −1.09 to −0.20), 6 weeks (SMD = −0.72, 95% CI = −1.15 to −0.29), and 8 weeks (SMD = −0.50, 95% CI = −0.71 to −0.29) compared to control group. Pregabalin also showed a significant greater improvement in anxiety (Mean Difference (MD) = −1.38, 95% CI = −1.74 to −1.02, p < 0.00001), depression (MD = −1.40, 95% CI = −1.71 to −1.08, p < 0.00001), quality of life (SMD = 0.22, 95% CI = 0.07 to 0.37, p = 0.003) and sleep quality (SMD = −0.61, 95% CI = −0.87 to −0.36, p < 0.00001). There were no significant differences regarding disability and adverse events.ConclusionPregabalin in the treatment of neuropathic LBP demonstrated significant improvements in pain relief, associated symptoms of anxiety and depression, and enhancements in quality of life and sleep quality. In addition, it exhibits a favorable safety profile. Nevertheless, these findings should be interpreted with caution due to the limited quality of the evidence and the inadequate reporting of pain etiology in several included studies.